Desempenho físico de equinos soropositivos para anemia infecciosa equina - Debora Roque dos Santos (2018)
Equine Infectious Anemia (EIA) is an incurable disease in equids, being endemic in the Pantanal mato-grossense region, where the disease control through euthanasia of seropositive animals is not mandatory. EIA-carrier equines are routinely used at work for beef cattle farming, which is the regions main economic activity. The objective of this study was to assess the athletic performance of EIA-seropositive animals and obtain data to incentive disease control in the region. We used 16 male Pantaneiro equines between 10 and 16 years old, being eight seronegative (G1) and eight seropositive (G2) for EIA. Both groups were kept separately, at a distance of over 200 meters, in nearby farms in the Nhecolândia region of Pantanal. They were kept free in natural pasture with mineral salt and water ad libitum. Tests were performed before (T1) and after (T2) 42 days of physical training. Tests included progressive effort on a plane 1500-meter grass track, with the same horseman guiding each horse in jog, trot, canter and gallop gaits. During tests, all animals wore heart rate monitors and at the end of each step we registered their heart rate (HR) and blood lactate concentration ([La]). When an animal reached a [La] equal to or higher than 4 mmol/L and HR over 150 bpm, the test was interrupted. The distance covered (DC) was measured by GPS, being the sum of all distances from the test start until it was interrupted. Hematocrit (Ht), total protein (PT), triglicerid (Tg) and uric acid (UA) was evaluated at rest and 0, 10, 30 and 60 min after the tests, along with HR, RR and temperature rectal. To evaluate creatine kinase (CK), aspartate aminotransferase (AST) and lactate dehydrogenase (LDH), samples were collected at rest and 6, 12 and 24 hours after the test. The training protocol was: work in alternate days for 1 h between walk and canter being an individual gallop speed, corresponding to the VLa3 of the 1st test. The individual canter speed was determined as the speed at which the animal reached 3 mmol/L of [La] in the first test. In both test, the DC was longer (p<0.05) in G1 animals. In T1, there was no difference between G1 and G2 regarding Ht, HR and [La], however, in T2, animals from G2 had lower (p<0.05) Ht, FC e [La]. Higher values of Tg were observed in T1 in relation to T2 and there was a reduction in UA concentration in both experimental groups. There was no indication of muscle injury. The results indicate the EIA affects the functional performance of Pantanal equines, whose main function in the region is the work in the cattle handling, and for that reason, its control in the Pantanal of Mato Grosso is important